2020
DOI: 10.3390/joitmc6010003
|View full text |Cite
|
Sign up to set email alerts
|

Human Resources Readiness for Industry 4.0

Abstract: Industry 4.0 is related to major changes, particularly in production. As such changes might have major implications for the labour market; the paper focuses on the assumptions of the human capital and its preparedness for Industry 4.0 in the Czech Republic. The findings are based on EUROSTAT, MEYS, OECD, ISCED, CZSO, and WEF. Based on such data, twelve indicators were selected and described in the results. Subsequently, the correlation analysis was carried out, using the data of the Czech Republic in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 37 publications
5
53
0
2
Order By: Relevance
“…The above analyses are also confirmed by studies conducted by Vrchota et al (2020) who identified the areas that make it possible to improve the quality of human capital so that it is better prepared for the introduction of Industry 4.0. In addition, Gudanowska et al (2018) stated that employees should have both greater professional knowledge and technical skills when it comes to Industry 4.0.…”
Section: Results Findings and Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The above analyses are also confirmed by studies conducted by Vrchota et al (2020) who identified the areas that make it possible to improve the quality of human capital so that it is better prepared for the introduction of Industry 4.0. In addition, Gudanowska et al (2018) stated that employees should have both greater professional knowledge and technical skills when it comes to Industry 4.0.…”
Section: Results Findings and Discussionsupporting
confidence: 58%
“…Education and further professional development are also essential key factors for achieving the goals of Industry 4.0, which significantly changes the professional skills of employees in many areas (Hariharasudan and Kot 2018;Vrchota et al 2020). As noted in the research of Liczmańska-Kopcewicz and Wiśniewska (Liczmańska-Kopcewicz and Wiśniewska 2019), there is a positive correlation between the assessment of the degree of implementation of the innovation strategy, including technological innovation, and the assessment of the level of exploration and the use of knowledge about buyers and the introduction and use of new technologies.…”
Section: Background and Revolution Of Industry-literature Reviewmentioning
confidence: 99%
“…The effectiveness of the noted aspects of competition on this market is moderated by the importance of JC-WPs for potential applicant, as well as by the importance of the specific demands for jobs in comparison to the more general demands considered in the present study. Previous specialists argued that more corporations need to make their human resource management practices and the related reporting sustainable, ready to transition to the so-called "Industry 4.0", and more process oriented [87][88][89][90]. The results of the present study question whether JC-WPs of the world's top mining companies serve these needs.…”
Section: How Realistic Are the Expectations?mentioning
confidence: 78%
“…Following each researcher's point of analysis, digital economy and its competitiveness have been examined through information economy (Elsner et al 2015;Sun et al 2017;Trushkina 2019), implementation of the digital market (Gupta and Bose 2019; Lutz 2019), Industry 4.0 (Dzwigoł et al 2020; Hubert Backhaus and Nadarajah 2019; Kumar and Kumar 2019;Lenart-Gansiniec 2019;Sanghavi et al 2019;Vrchota et al 2019; Zupan Korže 2019) and new sources of gaining competitive advantage (Hoła et al 2015;Kuzior et al 2019;Miśkiewicz 2019;Shank and Gott 2019;Zhao et al 2019). Such aspects, as well as many others related to digital competitiveness, have been used in competitiveness rankings (IMD 2018;WEF 2018) and the formation of the Digital Transformation Scoreboard developed by the European Union (EC 2018).…”
Section: ) •mentioning
confidence: 99%